Evaluation of a piloted digital reproductive health registry in Jordan to improve mother and child health - Amiri, Mirwais; Al-Soukhni, Majd; Tahtamouni, Manal; Al Nsour, Mohannad (Reproductive health, 2025)
Background Primary data on antenatal care services in Jordan are stored in diverse systems among hospitals and Mother & Child Health (MCH) centers. The resulting information flow gaps between healthcare levels challenge the quality and continuity of MCH care. To close these data and care delivery gaps, a harmonized Reproductive Health Registry ( h RHR) was designed and piloted to bring data in a consistent/digital/readily accessible format and enhance the current health information system. Our study evaluated the perceptions on the newly developed h RHR’s improvement of the delivery of sexual and reproductive health (SRH) services in 19 healthcare centers where the h RHR was piloted. Methods We utilized a mixed methodology (qualitative and quantitative assessments). Three tools were used for Key Informants/stakeholders, services providers, and women. Results A total of 13 SRH stakeholders, 37 service providers, and 855 women/service users participated in this evaluation. All SRH stakeholders agreed that the h RHR is responding to a need for digitalization of routine MCH data, medical files, and reports. They all agreed that the synchronization with the currently used Computerized Patient Record System (CPRS) and the h RHR Web-based application will enhance the expansion and needed upgrades in the future. For service providers, 73% were satisfied with the system, 78.4% were willing to keep using it, and 81.1% indicated that the h RHR is highly useful to health providers. For women/service users, 89.2% agreed/strongly agreed that the new system improves the confidentiality and privacy of their health information, and 89.7% agreed/strongly agreed that the new system allows health staff to easily access patient information. There were also foreseeable challenges including fragmentation of electronic data management, lack of connectivity across health services, limited ownership, dependence on external funding as impeding factor for scalability, poor IT infrastructure still disrupting service in MCH centers and affecting data entry, and limited electronic connectivity/reporting access impacting the continuity of care. Conclusion The new h RHR has a high acceptance level among stakeholders, health providers and women using MCH services. The evaluation showed that the system improved documentation of data, decreased time, and effort of data reporting and retrieval, and improved access to patient data. Plain Language Summary In Jordan, health information about the services provided to pregnant women is scattered across different systems in various hospitals and centers, leading to gaps in information flow and challenges in providing consistent care to those women. Therefore, a new system called the harmonized Reproductive Health Registry ( h RHR) was created to organize and improve access to this data in one easy-to-use digital format. To see how this new system affected the healthcare provided to women, the new system was implemented and tested in 19 health centers. We used different methods, like interviews and surveys, to collect feedback from 13 high level personnel involved in sexual and reproductive health, 37 healthcare workers who were using the new system, and 855 women who benefited from the provided services. All participants expressed their consensus on the new system's effectiveness in organizing information and medical records digitally. The majority of healthcare workers expressed satisfaction and a willingness to continue using it, and most women believed it enhanced the privacy of their health information while facilitating easier access for staff. There were also foreseeable challenges for the implementation and scaleup of the new electronic data management system due to the poor/limited technology infrastructure and existing dependence on external funding. In summary, the new system received positive feedback overall and was perceived as an improvement for quicker and more efficient recording and retrieval of patient information services.